Adaptive Organizations - Dessein, Wouter; Santos, Tano (Journal of Political Economy, 2006)
We consider organizations that optimally choose the level of adaptation to a changing environment when coordination among specialized tasks is a concern. Adaptive organizations provide employees with flexibility to tailor their tasks to local information. Coordination is maintained by limiting specialization and improving communication. Alternatively, by letting employees stick to some preagreed action plan, organizations can ensure coordination without communication, regardless of the extent of specialization. Among other things, our theory shows how extensive specialization results in organizations that ignore local knowledge, and it explains why improvements in communication technology may reduce specialization by pushing organizations to become more adaptive.